2023
DOI: 10.1039/d2ra07411g
|View full text |Cite
|
Sign up to set email alerts
|

Visible light-induced oxidative α-hydroxylation of β-dicarbonyl compounds catalyzed by ethylenediamine–copper(ii)

Abstract: An efficient visible light-induced oxidative α-hydroxylation of β-dicarbonyl compounds has been developed using structurally simple ethylenediamine–copper(ii) as a catalyst.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 38 publications
0
1
0
Order By: Relevance
“…In 2023, based on the understanding of the activation properties of bisoxazoline metal complexes, Wang, Chu, Li et al reported a reaction using ethylenediamine-copper(II) as a catalyst and only requiring 0.01 mol % tetraphenyl-porphyrin (TPP) to perform α-hydroxylation of β-ketoesters in THF (Scheme 11). [20] The reaction utilizes oxygen from the air as the oxygen source and can efficiently convert raw materials into the corresponding target products in a short time. The researchers conducted gram-scale experiments, achieving a high yield of 97 % for the α-hydroxylated product, demonstrating the practical potential of the reaction.…”
Section: α-Hydroxylation Mediated By Oxygen Involvementmentioning
confidence: 99%
“…In 2023, based on the understanding of the activation properties of bisoxazoline metal complexes, Wang, Chu, Li et al reported a reaction using ethylenediamine-copper(II) as a catalyst and only requiring 0.01 mol % tetraphenyl-porphyrin (TPP) to perform α-hydroxylation of β-ketoesters in THF (Scheme 11). [20] The reaction utilizes oxygen from the air as the oxygen source and can efficiently convert raw materials into the corresponding target products in a short time. The researchers conducted gram-scale experiments, achieving a high yield of 97 % for the α-hydroxylated product, demonstrating the practical potential of the reaction.…”
Section: α-Hydroxylation Mediated By Oxygen Involvementmentioning
confidence: 99%